1991
DOI: 10.1128/aac.35.10.2155
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance to multiple drugs by introduction of the Enterobacter cloacae romA gene into OmpF porin-deficient mutants of Escherichia coli K-12

Abstract: Introduction of the romA gene cloned from Enterobacter cloacae into Escherichia coli K-12 resulted in almost complete inhibition of OmpF expression and a concomitant increase in resistance to quinolones, beta-lactams, chloramphenicol, and tetracyclines. In addition, the romA gene reduced the susceptibility to these multiple drugs even in the OmpF porin-deficient mutants of E. coli K-12. Results indicate the presence of romA-sensitive penetration pathway(s) for these multiple drugs other than the OmpF porin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Kp342 encodes ramA (KPK_4028), a gene previously identified in K. pneumoniae that confers resistance to chloramphenicol, tetracycline, nalidixic acid, ampicillin, norfloxacin, trimethoprim and puromycin A when expressed in E. coli K12 [73] . Immediately upstream of this gene is romA (KPK_4029), which was originally isolated from Enterobacter cloacae as a gene that when expressed in E. coli , caused reduced expression of outer membrane proteins, resulting in a multiple drug resistance phenotype (quinolones, beta-lactams, chloramphenicol, and tetracycline) [74] that is independent of OmpF [75] . This gene has recently been shown to be adjacent to ramA in K. pneumoniae G340 during the sequencing of a tigecycline susceptible transposon mutant clone in ramA [76] .…”
Section: Resultsmentioning
confidence: 99%
“…Kp342 encodes ramA (KPK_4028), a gene previously identified in K. pneumoniae that confers resistance to chloramphenicol, tetracycline, nalidixic acid, ampicillin, norfloxacin, trimethoprim and puromycin A when expressed in E. coli K12 [73] . Immediately upstream of this gene is romA (KPK_4029), which was originally isolated from Enterobacter cloacae as a gene that when expressed in E. coli , caused reduced expression of outer membrane proteins, resulting in a multiple drug resistance phenotype (quinolones, beta-lactams, chloramphenicol, and tetracycline) [74] that is independent of OmpF [75] . This gene has recently been shown to be adjacent to ramA in K. pneumoniae G340 during the sequencing of a tigecycline susceptible transposon mutant clone in ramA [76] .…”
Section: Resultsmentioning
confidence: 99%
“…Komatsu et al (11) reported that introduction of the romA4 gene of Enterobacter cloacae into Escherichia coli resulted in resistance to ampicillin, cephems, quinolones, tetracyclines, and chloramphenicol, with the concomitant appearance of a new outer membrane protein. Nicas and Hancock (13) also reported that overexpression of outer membrane protein Hi in P. aeruginosa resulted in decreased susceptibilities to gentamicin, polymyxin B, and EDTA.…”
Section: Resultsmentioning
confidence: 99%
“…RamA is thought to form an operon with a gene specifying the outer membrane protein RomA. RamA acts as a transcriptional activator, while RomA is a putative channel-forming protein (7,14) somehow involved in the resistance phenotype. The role of ramA in the antibiotic resistance phenotype of clinical strains has not been described.…”
mentioning
confidence: 99%